Where else in the wild? : more camouflaged creatures concealed-- and revealed - Schwartz, David M. (Tricycle Press, 2009)
"Each of the camouflaged creatures on these pages, from chickadees to crayfish, is disguised for a reason. Some are on the prowl for prey, while others hide from hungry predators. Discover why geckos have a spooky reputation; why it pays for a mouse to have a dark-colored back and light-colored belly; and why you wouldn't want to be fooled by a scorpion fish. In this follow-up to the acclaimed Where in the Wild?, David Schwartz, Yael Schy, and Dwight Kuhn take readers on another remarkable tour through the fascinating world of animal camouflage"--Publisher description.